Designations of Speed Derived from Verbs of Motion (Based on Vocabulary of Russian Folk Dialects) - E. O. Borisova (Научный диалог)
The article refers to the Russian dialect items, naming the speed of an action or movement. The Russian North lexis is mainly covered. Motivational analysis of the words is made, revealing the models of nomination of speed through naming of ways of moving: walking, running, flying, jumping, etc. Classification of main semantic types of verbs, which motivate linguistic units with the meaning of speed or sluggishness, is proposed. Word-forming structure of the derivatives, based on the most productive models, is described. Special attention is paid to the words with unclear internal form. During the analysis, the author concludes that the vocabulary of linear motion is highly productive in the nomination of speed. Frequent are the models of naming velocity though the capacity to move ( hodko ‘in a fast manner’, brodkiy ‘brisk, capable to walk a lot and fast’, etc.); stem reduplication in order to highlight the semantics of intensity ( begom begat’ ‘to do something fast and promptly’, letkom sletat’ ‘to walk fast’ etc.); extension of the meaning of verbs of movement and their derivatives, in other words, the use of the corresponding words to describe speed of any activity ( Ya segodnya nabegom propolola ).